Memorializing the GDR : monuments and memory after 1989 - Saunders, Anna 1976- (berghahn, 2018)
Since unification, eastern Germany has witnessed a rapidly changing memorial landscape, as the fate of former socialist monuments has been hotly debated and new commemorative projects have met with fierce controversy. Memorializing the GDR provides the first in-depth study of this contested arena of public memory, investigating the individuals and groups devoted to the creation or destruction of memorials as well as their broader aesthetic, political, and historical contexts. Emphasizing the interrelationship of built environment, memory and identity, it brings to light the conflicting memories of recent German history, as well as the nuances of national and regional constructions of identity